Lanthano phosphomolybdate-decorated silica nanoparticles: novel hybrid materials with photochromic properties. Issue 10 (5th February 2015) - Pinto, Tânia V.; Fernandes, Diana M.; Pereira, Clara; Guedes, Alexandra; Blanco, Ginesa; Pintado, Jose M.; Pereira, Manuel F. R.; Freire, Cristina
Abstract : Novel hybrid nanomaterials prepared through the immobilization of phosphomolybdates onto functional silica nanoparticles revealed promising photochromic properties under UV irradiation. Abstract : Novel photochromic hybrid nanomaterials were prepared through the immobilization of the lacunary Keggin-type phosphomolybdate (TBA4 H3 [PMo11 O39 ]· x H2 O, denoted as PMo11 ) and sandwich-type lanthano phosphomolybdates (K11 [Ln III (PMo11 O39 )2 ]· x H2 O, denoted as Ln(PMo11 )2, where Ln III = Sm, Eu, Gd, Tb and Dy) onto positively-charged functionalized silica nanoparticles. The functionalized silica nanoparticles were prepared by a one-step co-condensation route between tetraethyl orthosilicate and dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, presenting an average particle size of 95 ± 26 nm, a spherical morphology and a pore diameter of 13.7 nm. All characterization techniques proved the successful immobilization of the phosphomolybdates. The photochromic properties of the resulting hybrid nanomaterials in the solid state were evaluated by UV-Vis spectroscopy and colorimetry. All materials revealed promising photochromic properties under UV irradiation ( λ = 254 nm). The lacunary phosphomolybdate anchored onto the silica nanoparticles, C18-SiO2 @PMo11, showed the best photoswitching properties, with the color changing from green to dark-blue (Δ E * = 26.8). Among the Ln(PMo11 )2 -based hybrid nanomaterials, those containing higher Mo loadings – Eu III - and Tb III -based samples – presented more significant color changes from green to dark-blue (Δ E * = 18.8–18.9). These results revealed that the optical properties of the as-prepared hybrid nanomaterials did not depend directly on the type of Ln III cation, but only on the amount of Mo, which was the target element responsible for the photochromic behavior.